Analisis Manajemen Risiko Finansial pada Startup Pengolahan Limbah Plastik Berbasis Inovasi - Maryam; Nengsih, Rita; Hanum, Filia; Khairuna; Humaira, Ajrina (Jurnal Serambi Engineering, 2025)
Innovative plastic waste recycling startups play a crucial role in promoting the circular economy and sustainable development. However, this sector faces various complex financial risks, including high initial investment requirements, market fluctuations, liquidity constraints, and regulatory uncertainty. This article aims to analyze the main categories of financial risks faced by plastic recycling startups and identify effective mitigation strategies based on recent literature reviews. Using a qualitative approach through an extensive review of international sources such as OECD, UNIDO, and IFC, the study reveals that initial investment and liquidity risks have the highest probability and impact on business sustainability. Effective mitigation strategies include funding diversification (via venture capital, green crowdfunding, and green financing), technology-based operational efficiency, and the implementation of digital cash management systems. Furthermore, external actors particularly governments, financial institutions, research bodies, and NGOs play a significant role in strengthening startups’ financial resilience through regulation, financing, innovation, and advocacy support. This study highlights the importance of integrating technological innovation with financial risk management as a foundation for sustainable eco-friendly startups while addressing the existing research gap on financial risk management in the recycling sector of developing countries